Forest and civilisations - Yasuda, Yoshinori; Yasuda, Yoshinori; Yangtze River Civilisation Programme (New Delhi : Roli Books, 2001)
Contributed articles on the relationship between the forest and the human community, reflecting upon our current understanding of civilisations.
"Yangtze River Civilisation Programme (YRCP)."
Includes bibliographical references.
Keywords: Ecology; Forest ecology